Different risk profiles of biologic agents for new-onset psoriasis in patients with rheumatoid arthritis - Baganz, L.; Listing, J.; Kekow, J.; Eisterhues, C.; Wassenberg, S.; Zink, A.; Strangfeld, A. (Semin Arthritis Rheum, 2020)
OBJECTIVE: To investigate rates and risk factors for incident and recurrent psoriasis in rheumatoid arthritis (RA) patients treated with different biologic (b) and conventional synthetic (cs) disease-modifying antirheumatic drugs (DMARDs). METHODS: RA patients enrolled in the German biologics register RABBIT without (n = 14,525) or with a history of psoriasis (n = 375) were analyzed separately. All first events of psoriasis reported until October 2017 were assigned to the treatments prescribed in the previous 3 months. Crude incidence rates (IR) of psoriasis were calculated per 1000 patient-years. To investigate risk factors for psoriasis, cox regressions with and without inverse probability weights were applied to adjust for confounding by indication. RESULTS: 117 incident and 37 recurrent psoriatic events were reported. Patients exposed to TNFi had a significantly higher incidence rate (IR = 3.04/1,000 PY) than those exposed to csDMARDs only (IR = 0.65), whereas IRs for abatacept, rituximab and tocilizumab did not differ significantly from csDMARDs. Adjusted Cox regression confirmed a higher risk for TNFi. Female sex (HR: 1.7) and smoking (HR: 2.1) were significantly associated with incident psoriasis while methotrexate decreased the risk (HR: 0.5). For recurrent psoriasis, IRs for TNFi, abatacept and rituximab were significantly higher than for csDMARDs. CONCLUSIONS: Our data confirm a previously observed increased risk of incident psoriasis in patients exposed to TNFi compared to csDMARDs. However, the overall risk is low and the event is usually non-serious. Comedication of TNFi with methotrexate seems to lower the risk of incident psoriasis. In patients with a history of psoriasis, recurrence as adverse event is rare.